(untitled) - Mann, James G. (New York, 1999)
In the U.S. alone, process industries, petrochemicals, pulp and paper, metals and minerals, and many others u will generate over 120 million tons of wastewater by the year 2000. Industrial Water Reuse and Wastewater Minimization, by James G. Mann and Y.A. Liu, describes water reuse and wastewater minimization principles and practices that can be used worldwide. Relatively easy to use and surprisingly inexpensive, the methods youAEll find in this important guide - particularly water-pinch technology u are not only ecologically sound, but significantly lower manufacturing costs. Concepts are illustrated with abundant charts, tables, and real-life case studies.
Kỹ thuật xử lý nước thải và nước cấp nâng cao
Keywords: Industrial water supply - management,Water reuse